ChemInform Abstract: New Alkaloids and α‐Glucosidase Inhibitory Flavonoids from Ficus hispida. Issue 36 (August 2016) - Shi, Zheng‐Feng; Lei, Chun; Yu, Bang‐Wei; Wang, He‐Yao; Hou, Ai‐Jun
Abstract: isolation and structure elucidation of four new alkaloids, ficushispimine A (I), ficushispimine B (II), ficushispimine C (III), and ficushispidine (IV)